Neurotoxicity Induced by Ertapenem in Patients of a General Hospital - Cámara-Reyes, Ramón Rolando (2026)
Objective: To describe the clinical characteristics and risk factors related to ertapenem-induced neurotoxicity in patients at a Peruvian hospital. Methods: A retrospective case series study was conducted, including seven cases recorded between 2023 and 2024. Neurotoxicity was defined as the presence of confusion, hallucinations, delirium, or other neurological symptoms that were resolved after discontinuing or substituting the antibiotic. Medical history, renal function, serum albumin, and hemoglobin levels were analyzed, and the Naranjo Scale was applied to assess the probability of causality. Results: Patients were over 60 years old with comorbidities such as hypertension (85.7%), chronic kidney disease (71.4%), and diabetes mellitus (57.14%). Neurological symptoms appeared on average 5.7 days after starting treatment, with confusion and psychomotor agitation being the most frequent. The average duration of ertapenem use was 7 days, and symptoms took 4.1 days to resolve after drug discontinuation. All cases were classified as "probable" according to the Naranjo Scale. Conclusion: Ertapenem-induced neurotoxicity was related to factors such as renal disease, hypoalbuminemia, and advanced age. Dose adjustment and monitoring of risk factors are recommended to minimize complications and optimize its use in clinical practice.